2019
DOI: 10.1177/1071100719858309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Chronic Lateral Ankle Instability and Hindfoot Varus Using Weight-Bearing Cone Beam Computed Tomography

Abstract: Background: Varus hindfoot deformity may increase the risk of chronic lateral ankle instability (CLAI). Our aim was to analyze hindfoot alignment (HFA) in patients with CLAI using weight-bearing cone beam computed tomography (WBCT) to assess this risk. Methods: This retrospective, comparative analysis was carried out using an existing WBCT database (Talas, CurveBeam LLC), including data sets for 370 consecutive feet (189 patients) obtained between July 2016 and October 2018 at a single institution. The softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Negative measurements indicate varus alignment (center of the ankle positioned laterally to the bisecting line of the foot tripod), while positive values represent valgus alignment (center of the ankle joint located medially to the bisecting line of the foot tripod). 6,13,29,31,44 For this study, the mean FAO of included patients and 95% confidence intervals (95% CIs) were calculated. Patients with residual varus and valgus malalignment were identified as those with FAO values outside the 95% CI of the patient’s cohort, higher for valgus and lower for varus.…”
Section: Methodsmentioning
confidence: 99%
“…Negative measurements indicate varus alignment (center of the ankle positioned laterally to the bisecting line of the foot tripod), while positive values represent valgus alignment (center of the ankle joint located medially to the bisecting line of the foot tripod). 6,13,29,31,44 For this study, the mean FAO of included patients and 95% confidence intervals (95% CIs) were calculated. Patients with residual varus and valgus malalignment were identified as those with FAO values outside the 95% CI of the patient’s cohort, higher for valgus and lower for varus.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also documented how the foot morphotype measurements used in this study (such as the FAO, the CO, the HAA, the Inftal-Suptal angle, the Inftal-Hor angle, the FAA, the navicular-to-floor distance and the medial cuneiform-to-floor distance) provide high intra-and inter-observer reliability. 10,11,14,15 Our comparative study showed that symptomatic professional male football players within the National Football League have a normally aligned hindfoot with a more pronated forefoot when compared to healthy controls, as demonstrated by significant differences in FAA, navicular-to-floor and medial-cuneiform-to-floor distance. However, although we could not perform a formal statistical analysis including data reported by other authors, values for these measurements from NFL players were still far higher than historical flatfeet (Table 2).…”
Section: Discussionmentioning
confidence: 69%
“…17 Given the complexity of cavovarus foot deformity and surgical reconstruction, we believe further consideration should be given to in-depth study with WBCT. In this vein, Lintz et al 15 recently demonstrated that WBCT was used to make an association between hindfoot varus and chronic lateral ankle instability.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of this modality permits accurate assessment of complex foot deformity 3-dimensionally, such as pes planovalgus and hallux valgus. 4,[6][7][8][9]11,13,15 WBCT overcomes the well-documented operator and anatomical biases of previous modalities such as projection and rotation issues, 2,3,23 and standardized 3-dimensional biometrics have been validated to study hindfoot deformity. 16 WBCT has also been found to be more accurate than traditional CT for evaluation of the foot and ankle.…”
Section: Introductionmentioning
confidence: 99%